2015
DOI: 10.1088/0004-637x/806/2/255
|View full text |Cite
|
Sign up to set email alerts
|

On Origin and Destruction of Relativistic Dust and Its Implication for Ultrahigh Energy Cosmic Rays

Abstract: Dust grains may be accelerated to relativistic speeds by radiation pressure, diffusive shocks, and other acceleration mechanisms. Such relativistic grains have been suggested as primary particles of ultrahigh energy cosmic rays (UHECRs). In this paper, we first revisit the problem of acceleration by radiation pressure and calculate maximum grain velocities achieved. We find that grains can be accelerated to relativistic speeds with Lorentz factor γ < 2 by powerful radiation sources, which is lower than earlier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 92 publications
0
41
0
Order By: Relevance
“…This RAT alignment time is another important parameter that should be considered for the measurements of the variations of polarization from the material surrounding a supernovae. From Hoang (2017) it is shown that for a cloud at distance d ∼ 1 − 10 pc (i.e., well beyond the sublimation radius, see Hoang et al 2015), the a ∼ 0.03 µm grains can be radiatively aligned on t spin−up ∼ 0.3 − 30 days for L SN = 10 8 L .…”
Section: Measuring the Polarization In The Vicinity Of Novae And Supementioning
confidence: 99%
“…This RAT alignment time is another important parameter that should be considered for the measurements of the variations of polarization from the material surrounding a supernovae. From Hoang (2017) it is shown that for a cloud at distance d ∼ 1 − 10 pc (i.e., well beyond the sublimation radius, see Hoang et al 2015), the a ∼ 0.03 µm grains can be radiatively aligned on t spin−up ∼ 0.3 − 30 days for L SN = 10 8 L .…”
Section: Measuring the Polarization In The Vicinity Of Novae And Supementioning
confidence: 99%
“…(see Hoang et al 2015), and this cloud may be ejected as well. The ejecting cloud would collide with another cloud in its vicinity (e.g., for SN 1986G and 2014J), which certainly results in destruction of big grains.…”
Section: Simulation-based Inversion Techniquementioning
confidence: 99%
“…Moreover, bombardment of fast heavy ions can eject target nuclei through a process so-called electronic sputtering (Hoang et al 2015). For our high energy case, this process is shown to be inefficient and yields a rather low sputtering yield.…”
Section: Heavy Ion Bombardmentmentioning
confidence: 88%
“…Here S max is the maximum tensile strength of the material that can reach S max ∼ 10 11 dyn cm −2 for ideal material (see Hoang et al 2015). Thus, spacecraft damage by Coulomb explosions can be neglected.…”
Section: Maximum Surface Electric Potential and Coulomb Explosionsmentioning
confidence: 99%